Effects of isolation technique and conditions on the extractability, physicochemical and functional properties of pigeonpea (Cajanus cajan) and cowpea (Vigna unguiculata) protein isolates. II. Functional properties - A Mwasaru, Mwanjala; Muhammad, Kharidah; Bakar, Jamilah; Che Man, Yaakob (Elsevier, 1999)
The functional properties of pigeonpea and cowpea protein isolates were determined as a function of extraction technique and pH conditions of the extraction medium. The isolates extracted using the micellization technique (MP) showed significantly (P<0.05) higher solubility than those extracted using the isoelectric point precipitation technique (IP) and, for the latter, solubility was negatively correlated with the extraction pH. The MP isolates exhibited significantly higher water absorption than the isoelectric isolates extracted at pH 8.5 but lower than the isolates extracted at pH 11.5 and 12.5. Cowpea MP exhibited higher oil absorption than the IP but pigeonpea MP was lower in this property than the IP extracted at pH 8.5 and higher than those extracted at pH 9.5–11.5. The MP isolates exhibited better emulsifying properties than the corresponding IP isolates and this property was drastically impaired at extraction pH 12.5. Pigeonpea MP exhibited lower foam expansion than the IP isolates except for the isolate extracted at pH 12.5, but was higher in foam stability. Cowpea MP showed higher foam expansion than the IP isolates which decreased with increasing extraction pH for the latter, but foam stability was only slightly affected. The MP isolates exhibited better gelation properties than the IP isolates extracted at pH above 9.5 and the least gelation concentration increased with increasing extraction pH. The solubility and exposed hydrophobicity best predicted the whipping properties, emulsion stability, and least gelation concentration of the isolates.